2020
DOI: 10.1136/svn-2019-000289
|View full text |Cite
|
Sign up to set email alerts
|

Serum bilirubin and ischaemic stroke: a review of literature

Abstract: Bilirubin, a product of heme metabolism, is the most potent endogenous antioxidant which increases in many oxidative stress conditions such as stroke. It has been widely known to exert neuroprotective effect on stroke through mechanisms involved in development, therefore, it can influence the occurrence and prognosis of ischaemic stroke (IS). In this review, studies were identified by a comprehensive search of Pubmed, Embase, the Cochrane Library (Cochrane Database of Systematic Reviews, Cochrane Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“… 9 Previous studies reported that bilirubin exhibits both neurotoxic and neuroprotective effects after ischemic stroke, without reaching a consensus for the prognosis of ischemic stroke. 10 However, these studies almost merely concentrated on one of the subtypes of bilirubin, without distinguishing the difference among them. To the best of our knowledge, studies on the predictive value of TBIL, DBIL, and IBIL for the clinical outcomes in patients diagnosed with AIS receiving intravenous thrombolysis are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Previous studies reported that bilirubin exhibits both neurotoxic and neuroprotective effects after ischemic stroke, without reaching a consensus for the prognosis of ischemic stroke. 10 However, these studies almost merely concentrated on one of the subtypes of bilirubin, without distinguishing the difference among them. To the best of our knowledge, studies on the predictive value of TBIL, DBIL, and IBIL for the clinical outcomes in patients diagnosed with AIS receiving intravenous thrombolysis are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, a small number of studies showed only moderately positive or null relationship [27,28]. In addition, as described in our previous published review, the relationship between bilirubin and stroke risk may be influenced by gender and stroke types [22]. In this article, we also reviewed the relationship between bilirubin and stroke prognosis.…”
Section: Mini Reviewmentioning
confidence: 77%
“…In 2017, our study group performed a systemic review and meta-analysis of 11 population-based observational studies involving 5,060 stroke cases among 131,450 subjects investigating the relationship between total serum bilirubin and risk for stroke, supporting an inverse association between serum total bilirubin and risk for IS and AS in males [12]. A large number of studies showed that bilirubin is involved in antioxidation defense mechanisms and a higher level of serum bilirubin in the normal range was associated with a decreased risk of IS [22]. In order to make this issue more accurate, we conducted a dose-response meta-analyses to quantify the relationship between TBIL levels within physiologic range and risk of stroke in 2020, and it has been accepted by Chinese Circulation Journal and will soon be published online in April 2021.…”
Section: Mini Reviewmentioning
confidence: 93%
“…After stroke occurs, the negative influence of high levels of serum bilirubin on patients’ outcome possibly reflects the intensity of initial oxidative stress. Patients with AIS or TIA with higher levels of bilirubin had larger cerebral infarcts, more prominent brain oedema and more severe reperfusion injuries with poorer functional outcomes than those with lower bilirubin levels [ 3 , 28 ].…”
Section: Discussionmentioning
confidence: 99%